Impact of Transgenic Brassica napus Harboring the Antifungal Synthetic Chitinase (NiC) Gene on Rhizosphere Microbial Diversity and Enzyme Activities - Khan, Mohammad S.; Sadat, Syed U.; Jan, Asad; Munir, Iqbal (Frontiers in Plant Science, 2017)
Transgenic Brassica napus harboring the synthetic chitinase (NiC) gene exhibits broad-spectrum antifungal resistance. As the rhizosphere microorganisms play an important role in element cycling and nutrient transformation, therefore, biosafety assessment of NiC containing transgenic plants on soil ecosystem is a regulatory requirement. The current study is designed to evaluate the impact of NiC gene on the rhizosphere enzyme activities and microbial community structure. The transgenic lines with the synthetic chitinase gene (NiC) showed resistance to Alternaria brassicicola, a common disease causing fungal pathogen. The rhizosphere enzyme analysis showed no significant difference in the activities of fivethree soil enzymes: alkalyine phosphomonoestarase, arylsulphatase, and β-glucosidase, urease and sucrase between the transgenic and non-transgenic lines of B. napusbrassica varieties, Durr-e-NIFA (DN) and Abasyne-95 (AB-95). However, varietal differences were observed based on the analysis of molecular variance. Some individual enzymes were significantly different in the transgenic lines from those of non-transgenic but the results were not reproducible in the second trail and thus were considered as environmental effect. Genotypic diversity of soil microbes through 16S-23S rRNA intergenic spacer region amplification was conducted to evaluate the potential impact of the transgene. No significant diversity (4% for bacteria and 12% for fungal) between soil microbes of NiC B. napusbrassica and the non-transgenic lines was found. However, significant varietal differences were observed between DN and AB-95 with 79% for bacterial and 54% for fungal diversity. We conclude that the NiC B. napusbrassica lines may not affect the microbial enzyme activities and community structure of the rhizosphere soil. Varietal differences might be responsible for minor changes in the tested parameters.